Mexican financial development - Brothers, Dwight S.; Solís M., Leopoldo (Austin: University of Texas Press, 1966)
This is a fine addition to the growing body of literature on Mexican development. The authors begin with a synopsis of the pre-1940 financial system, pass on to their major task of describing and explaining Mexico's financial history in the 1940-1960 period, and conclude with a review of post-1960 developments. Their major task they divide into two parts. The first is a detailed descriptive history (by far the best yet published), of financial institutions, instruments, policies, and procedures. The second is a theoretical attempt to explain both the behavior of the monetary authorities and the growth of "financial intermediation." The authors argue convincingly that the power of the central bank to control the money supply using traditional quantitative controls is severely limited in a country like Mexico.
"The sections ... originally drafted in Spanish were translated into English by Marian Berdecio."
Bibliography: p. [209]-221.
rpm 02/05/2018
Loans
Keywords: Finance; Monetary policy; Saving and investment